Hydroxyl radical-initiated aging of particulate squalane. (15th September 2020) - Zhang, Bowen; Hu, Xiaoyu; Yao, Lei; Wang, Mingyi; Yang, Gan; Lu, Yiqun; Liu, Yiliang; Wang, Lin
Abstract: Heterogeneous aging of organic aerosols can significantly alter their physicochemical properties and thus their impacts on the radiative balance of the earth system. In this study, kinetics and mechanisms of heterogeneous reactions between suspended squalane particles and hydroxyl (OH) radicals were investigated using a self-made photooxidation flow tube and a high-resolution long time-of-flight chemical ionization mass spectrometer equipped with a Filter Inlet for Gases and AEROsols (FIGAERO-HR-LToF-CIMS). In addition to the measurements of the heterogeneous reaction rate constants for squalane and its multi-generation functionalization products whose carbon backbone are retaining, identification and semi-quantification of functionalization and fragmentation products from OH radical-initiated aging of squalane were carried out, which were utilized to develop a plausible reaction scheme. Our results show that the heterogeneous oxidation mechanism for particulate squalane is similar to those for OH radical initiated-oxidation of gaseous alkanes, but intermolecular hydrogen abstraction, in addition to reactions with O2, isomerization, and decomposition, could be an important heterogeneous reaction pathway for alkoxy radicals, leading to the formation of functionalization products of alcohols. The relative abundances of fragmentation products suggest that OH radicals preferably attack the tertiary carbon. The evolution of products indicates that functionalization plays a leading role in the early stage of the reaction and the fragmentation products become more and more important with increased OH exposure. Our study depicts heterogeneous reaction pathways of organic aerosols with OH radicals at the molecular level, and helps to better understand the chemical evolution of complex organic aerosols in the atmosphere. Highlights: Hydroxyl radical-initiated aging of particulate squalene was investigated. A plausible reaction scheme was developed. Intermolecular hydrogen abstraction is important for particulate alkoxy radicals. Functionalization plays a leading role in the early stage of the reaction.